Management of invasive group A streptococcal infections - Waddington, C.; Snelling, Thomas; Carapetis, J. (2014)
© 2014. Invasive group A streptococcal (GAS) disease in children includes deep soft tissue infection, bacteraemia, bacteraemic pneumonia, meningitis and osteomyelitis. The expression of toxins and super antigens by GAS can complicate infection by triggering an overwhelming systemic inflammatory response, referred to as streptococcal toxic shock syndrome (STSS). The onset and progression of GAS disease can be rapid, and the associated mortality high. Prompt antibiotics therapy and early surgical debridement of infected tissue are essential. Adjunctive therapy with intravenous immunoglobulin and hyperbaric therapy may improve outcomes in severe disease. Nosocomial outbreaks and secondary cases in close personal contacts are not uncommon; infection control measures and consideration of prophylactic antibiotics to those at high risk are important aspects of disease control. To reduce a substantial part of the global burden of GAS disease, an affordable GAS vaccine with efficacy against a broad number of strains is needed.